A profile monitoring of the multi-stage process. Issue 4 (4th July 2019) - Park, Changsoon; Tsui, Kwok-Leung
Abstract: The effective monitoring of the multi-stage process in the modern manufacturing and service processes is crucial in maintaining and improving the final output quality. The essential of the multi-stage process monitoring is to be able to give a signal at each single stage in order to avoid the delay in detecting assignable causes in the process. A multi-stage process is separated to a series of the single-stage processes, and each single-stage process is treated as a profile structure, whose quality is considered as the process output with inputs from the previous stage and the current stage. The EWMA chart is implemented to the profile process using the orthogonal design input. The true process output is often measured with errors because the complexity of the multi-stage process makes the true quality difficult to measure. The harmfulness of measurement errors in the multi-stage process is also investigated.